Identifying Iron-Bearing Nanoparticle Precursor for Thermal Transformation into the Highly Active Hematite Photo-Fenton Catalyst - Anna Šutka (Catalysts, 2020)
The hematite photo-Fenton catalysis has attracted increasing attention because it offers strong oxidation of organic pollutants under visible light at neutral pH. In the present work, aqueous synthesis of hematite photo-Fenton catalysts with high activity is demonstrated. We compare photo-Fenton activity for hematite obtained by hydrolyzation at 60 °C or by a thermally induced transformation from iron-bearing nanoparticles, such as amorphous iron oxyhydroxide or goethite. A link between their structure and visible light photo-Fenton reactivity is established. The highest activity was observed for hematite obtained from goethite nanowires due to oblong platelet-like structure, high surface area and the presence of nanopores.